KELINCAHAN STRATEGIS DALAM MEWUJUDKAN VISI PERUSAHAAN (Studi Kasus BPJS Ketenagakerjaan) - Tajuddin Akbar; Mahfudz Mahfudz (Jurnal Akuntansi dan Pajak, 2023)
The agility strategy is an important factor in accelerating growth and achieving the company's vision because implementing a strategy that is adaptive and in accordance with business needs can maintain the continuity of the company's business. It is also important to implement this in non-profit government institutions that manage employment social security programs because it carries the mandate to become a safety net so that new poverty is not created in Indonesia, so a strategic approach is needed that is oriented towards trust, sustainability and the welfare of workers in Indonesia, in accordance with the vision set by BPJS Ketenagakerjaan. This research is a qualitative research with descriptive analysis from the results of in-depth interviews with representative informants from internal and external institutions. The purpose of this study is to determine the achievement of the vision of BPJS Ketenagakerjaan and to identify how strategic agility is implemented to achieve the company's vision. The results of this study indicate that the Strategy Sensitivity aspect, Resource Fluidity aspect, Collective Commitment/Leadership Unity aspect, The Law of the Small Team aspect, The Law of Customer aspect and The Law of Network aspect are important aspects in implementing strategic agility in achieving the vision at BPJS Ketenagakerjaan, which in the end is to become provider of employment social security that trusted, sustainable and prosperous for Indonesian workers. Keywords: Agility strategy, Vision, Social Security, Employment, Strategic agility, trusted, sustainable, prosperous, BPJS Ketenagakerjaan.